A small estimated euro area model with rational expectations and nominal rigidities - Günter Coenen; Volker Wieland (European Central Bank (ECB), 2000)
In this paper we estimate a small model of the euro area to be used as a laboratory for evaluating the performance of alternative monetary policy strategies. We focus on the relationship between output and inflation and investigate the fit of the nominal wage contracting model due to Taylor (1980) and three different versions of the relative real wage contracting model proposed by Buiter and Jewitt (1981) and estimated by Fuhrer and Moore (1995a) for the United States. While Fuhrer and Moore reject the nominal contracting model in favor of the relative contracting model which induces more inflation persistence, we find that both models fit euro area data reasonably well. When considering France, Germany and Italy separately, however, we find that the nominal contracting model fits German data better, while the relative contracting model does quite well in countries which transitioned out of a high inflation regime such as France and Italy.
Keywords: E31; E52; E58; E61; 330; euro area; European Monetary Union; macroeconomic modelling; nominal rigidities; Rational Expectations